Lived religion, Pentecostalism, and social activism in authoritarian Chile: giving life to the faith - Florez, Joseph (Religion in the Americas, 2021)
In Giving Life to the Faith , Joseph Florez explores Pentecostal social engagement as it was folded into the extraordinary circumstances of everyday life during the Chilean military dictatorship (1973 - 1990). Florez traces Pentecostal activism, commonly portrayed as politically aloof or inert, through the life stories of the believers themselves and uncovers the logics of survival, resistance, and belief that sustained their work in the face of ubiquitous state repression. Using archival materials and Pentecostal oral histories, Florez brings Pentecostals' religious innovations and improvisations to the forefront of discussion and challenges observers of Latin American Pentecostalism to reconsider normative interpretations of the world's fastest growing religious movement